Food related risks during pregnancy: how much do women know about it? (Epidemiology, Biostatistics, and Public Health, 2022)
Aim Infection with Toxoplasma gondii and Listeria monocytogenes during pregnancy can lead to severe illness in the foetus but it can be prevented by simple hygienic measures. This study evaluated the knowledge that women have about food related risk and the information sources used.Methods We surveyed pregnant women and new mothers in[Removed for blind peer review], using a questionnaire approved by health direction, processed by an optical reader and analyzed using χ² test and Odds Ratio.Results 149 women responded to the survey, 78.5% of them received information from the gynaecologist, 45% from internet and then books/pamphlets. 67.8% felt well informed about food-related risks connected. 94% of them knows Toxoplasma; 39.5% ignore Listeria instead. From our results it’s evident  that graduated women tend to identify all foods as less secure and had better attitudes on cleaning refrigerator, on respecting temperatures, on avoiding consumption of undercooked foods, on protecting food before consumption.Conclusions Pregnant women have good awareness of food-related risks. However there’s a high confusion, due to the use of internet and other not reliable sources. This study demonstrates that it’s necessary to improve the organization of nutritional education by adequately trained health personnel.